The Influence of Training and Competence on Nurse Performance Over Organizational Commitment as an Intervening Variable - Irma Kartiani; Rina Anindita; Rokiah Kusumapradja (Penerbit Kemala Indonesia, 2020)
Nurse performance is very important in the process of patient service at the hospital. The poor performance of nurses will enable consumers to choose other hospitals that have a negative impact on the hospital's image. Therefore, competent nurses are needed to be able to provide excellent service to patients. Thus, to create competent nurses, a hospital should be improving competence by facilitating nurses by providing periodic training that is beneficial for nurses so that their work becomes effective and efficient. The purpose of this study aimed to prove the influence of training and competence on the performance of nurses in the hospitalized unit of Hermina Daan Mogot Hospital with organizational commitment as an intervening variable. In this research we use quantitative methods during survey at Daan Mogot Hospital. In this research the data taken from questionnaires on all nurses in the hospitalized units at Hermina Daan Mogot Hospital. The total population sampling in this study reached 76 nurses in the hospitalized unit in entire population. This study is using a simple regression test and t test where the results of the study indicate that training and competence have affect in the performance of nurses. However, training and competence do not affect organizational commitment, nor does organizational commitment affect nurses' performance. Thus, the research findings show that nurse performance is directly affected by training and competence without being influenced by organizational commitment while in different research models the organizational commitment can be a moderating variable between training and nurse performance.